Grundtvig og Brorson - Sørensen, Jørgen (Grundtvig-Studier, 1966)
Grundtvig and Brorson By Jørgen Sørensen Grundtvig’s evaluation of Br.’s hymns from 1828 remained unchanged. In Psalme-Blade, the collection which was to hold what was strictly necessary to meet the want, Gr. included only two by Br., although he knew him to be very popular in the “religious assemblies” and should have included more to be in agreement with his own view of the problem of the empty churches and the “religious assemblies” . In the “Prøvehefte” the number of hymns by Br. Was raised to seven, but judging from Fest-Psalmer Gr. finds himself able to recognize only three of them as real and important church hymns. Finally, when with Fest-Psalmer Gr. had the opportunity to organize all by himself what might eventually be called a complete hymn-book, there was room for only ten hymns by Br. out of a total number of 330. These collections of hymns are church hymn-books in the sense conveyed by Gr. in the following quotation, which is an answer to the complaint that the “Prøvehefte” was not also intended for family prayers: “Our remark in the preface about a church hymn-book has been completely misunderstood. We do not mean a book which could not be used outside the stone church, far from it; rather we have in mind a songbook aiming alone at what links us together in religious life and should be common to all who share the same faith and hope, so it was not an extrinsic but an intrinsic distinction we made between what belongs to the church and what to the home, as between what is objective and subjective in religiousness” . Thus, although the SV was not meant to be a church hymn-book in the ordinary sense, it was definitely a church hymn-book in Gr.’s sense as expressed above. It is to be regretted, then, that Gr. did not find occasion to work out the collection of hymns for private devotions which he had in mind in 1810-20 and which he also mentions to Fenger when devotional matter was left out of Psalme-Blade, because this would have given a more varied impression of Gr.’s evaluation of Br. But Gr.’s main interest definitely lay with the church, and the hymns in question— as he often points out— were easily accessible in many collections and older hymn-books. That is probably why he never did make the selection.